Europe's growth emergency - Zsolt Darvas; Jean Pisani-Ferry (Bruegel, 2011)
The European Union growth agenda has become even more pressing because growth is needed to support public and private sector deleveraging, reduce the fragility of the banking sector, counter the falling behind of southern European countries and prove that Europe is still a worthwhile place to invest. The crisis has a similar impact on most European countries and the US: a persistent drop in output level and a growth slowdown. This contrasts sharply with the experience of the emerging countries of Asia and Latin America. Productivity improvement was immediate in the US, but Europe hoarded labour and productivity improvements were in general delayed. Southern European countries have hardly adjusted so far. There is a negative feedback loop between the crisis and growth, and without effective solutions to overturn the crisis, growth is unlikely to resume. National and EU level policies should aim to foster reforms and adjustment and should not risk medium term objectives under the pressure of events. A more hands-on approach, including industrial policies, should be considered. Earlier versions of this Policy Contribution were presented at the Bruegel-PIIE conference on Transatlantic economic challenges in an era of growing multipolarity, Berlin, 27 September 2011, and at the BEPA-Polish Presidency conference on Sources of growth in Europe, Brussels, 6 October 2011.
Keywords: 330; Wirtschaftswachstum; Wachstumspolitik; Öffentliche Schulden; Investitionspolitik; EU-Staaten; Welt